Changes in feeling of connectedness among senior adolescents - Albina Kepalaitė (Social Welfare: Interdisciplinary Approach, 2014)
Adolescents who have low level of social connectedness more often distinguish themselves by nonadaptive, inappropriate behaviour. This study aims to disclose changes in connectedness due to application of play therapy in the senior adolescents’ group. Research results disclosed that application of play therapy method “Game of Life”, grounded on psychodrama principles, adjusted the feeling of social connectedness among senior adolescents: changes were observed in connectedness to self, at the social level and to the close friend. Application of play therapy resulted in more significant changes in social connectedness in the girls’ group than in the boys’ group. Social connectedness did not change comparing fifteen — eighteen-year-old adolescent’s groups.